Epidemiological, Clinical and Laboratory study of Canine Dermatophytosis in Baghdad Governorate, Iraq: Tareq Rifaaht Minnat1 and Jinan Mahmood Khalaf 2 - Minnat, Tareq Rifaaht (The Iraqi Journal of Veterinary Medicine, 2019)
The aim of the present study was to isolate and identify of the pathogenic fungi of canine dermatophytosis in Baghdad governorate Iraq, also study the epidemiology and describe the clinical signs of dermatophytosis, from January 2018 till December 2018. Out of 653 dogs 165 (25.3%) were with dermatomycoses and 103 (62.42%) dogs with dermatophytosis. The mycological diagnosis were conducted by direct microscopy and by culture the specimens on each sabouraud dextrose agar supplemented with chloramphenicol and cyclohxemide and dermatophytes test media. The identified dermatophytes were represented Microsporum sp.(80.6%) appeared Microsporum canis (87.9%); M. audounii (8.4% );M. gypseum (3. 6 %) and Trichophyton spp (19.4%) in which divided between Trichophyton ruburum (60.0 %) and T. terrestre (40.0%). Microsporum canis and Trichophyton ruburum were the most common species isolated (87.9%),(60.0 %) respectively. The overall prevalence of dermatomycosis and dermatophytosis from various parts region of Baghdad city were Al Karkh district (32.0%), (64.6%) and Al Rusafa district (22.4%), (60.4%) respectively. Moreover, a higher percentage of infection in young age 55 of 84 (65.47%) and lower infection in old age 8 of 18 (44.44%) with significant difference at P< 0.05. The effect of breeds on the prevalence of canine mycosis show high percentage of infection in German shepherd dog (47.96%) and lower infection in Bulldog breed (10.63%) as well as, high prevalence of dermatophytosis recorded in Rottweiler (100%), Pomeranian (83.3%) and lower prevalence (40.0 %) in each of Boxer and local dog breed. The relation of hair coat showed significantly high percentage of infection in long hair dogs (69.0%) than short hair coat (48.0%). There were no significant difference between the sex and habitat but, recorded a high (%) in shelters habitat (67.19%) and low (%) in plantation habitat (56.25%). The prevalence of infection was showed no signficantly high percentage of infection in cold climate winter (67.74%) in which low temperature and high humidity while low percentage of infection in dry climate autumn (44.4%). In addition the effect of season on the prevalence of dermatophytosis recognized by a higher (%) of infection in cold weather, winter (67.74%) and lower infection in dry weather, autumn (50.0%). Other dermatomycosis isolated were Chrysosporium Nannizziopsis dermatitidis (9.1%); Malassezia pacydermatis (7.9 %) and saprobe fungi from domestic dogs represented by Alternaria alternate (21.4%); Aspergillus spp (60.7%); Aspergillus flavus (25.9%); Aspergillus fumigatus (28.2%); Aspergillus niger (23.5 %); Aspergillus nidulans (22.4 %); Penicillium sp. (4.3%); Curvularia sp (3.6%) and Rhizopus sp (2.1%).